2002
DOI: 10.1038/sj.gene.6363866
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide screen for linkage in Nordic sib-pairs with multiple sclerosis

Abstract: 3p26.3, 3q21.1, 4q12, 6p25.3, 6q21, 9q34.3, 10p15, 11p15.5, 12q21.3, 16p13.3, 17q25.3,. Although none of these regions reaches the level of genome-wide significance, the number observed exceeds the 10 that would be expected by chance alone. Our results significantly add to the growing body of linkage data relating to multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 33 publications
3
40
0
2
Order By: Relevance
“…A region identified in the present study on chromosome 1q43-44 was also seen in the Italian screen, 14 and linkage at 4q31, 5q31, 7q33-34 and 18p11 was additionally observed in the American screen. 10 Similarly, our potential linkage on chromosome 16p matches that observed in the Nordic 13 and American screen, 10 as well as in a meta-analysis of the original American, Canadian and British linkage screens. 18 Since Australian MS linkage screen M Ban et al 16p was not identified in the two screens in Southern European populations, 14,15 this observation emphasises that alternate combinations of genes may determine susceptibility to multiple sclerosis in different populations (allelic and locus heterogeneity).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…A region identified in the present study on chromosome 1q43-44 was also seen in the Italian screen, 14 and linkage at 4q31, 5q31, 7q33-34 and 18p11 was additionally observed in the American screen. 10 Similarly, our potential linkage on chromosome 16p matches that observed in the Nordic 13 and American screen, 10 as well as in a meta-analysis of the original American, Canadian and British linkage screens. 18 Since Australian MS linkage screen M Ban et al 16p was not identified in the two screens in Southern European populations, 14,15 this observation emphasises that alternate combinations of genes may determine susceptibility to multiple sclerosis in different populations (allelic and locus heterogeneity).…”
Section: Discussionsupporting
confidence: 79%
“…16,17 As the number of observed peaks greatly exceeds that expected by chance at both MLSX0.7 and X1.8, it is likely that at least some of these regions harbour susceptibility genes. This interpretation is further supported by the fact that two of the four regions providing suggestive linkage have previously featured in multiple sclerosis genome screens: a regions close to chromosome 6q26 was observed in the UK, 9 American, 10 Nordic 13 and Italian 14 genome screens, whereas the suggestive linkage on chromosome Xp11 was previously reported in the UK screen. 9 Several of our regions of potential linkage also coincide with those suggested in previous multiple sclerosis genome screens.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…14 Furthermore, a Finnish group has narrowed down candidate region on chromosome 17q22-24 to 2.5 Mb, a distance quite affordable for candidate gene analysis with current molecular biology techniques. 15 The 2q23-31 region showed a lod score of B1.0 in the previous Nordic sib-pairs study 16 and was supported also in the Finnish study. 11 This region is at approximately 10 cM distant from the CTLA-4 gene, which, in previous studies from several groups, was reported to be associated with MS. [17][18][19] Figure 2 Haplotype-based TDT analysis results for chromosome 14.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, one of these studies was unable to detect a signal even from the MHC . Follow-up studies using multiply affected families also failed to detect any convincing new MS susceptibility loci (Kuokkanen et al, 1997;Coraddu et al, 2001;Akesson et al, 2002;Ban et al, 2002;Eraksoy et al, 2003). Adding more microsatellite markers to the initial genome screens also failed to produce new MS-associated genes Dyment et al, 2004b;Kenealy et al, 2004).…”
Section: Genomic Linkage Screensmentioning
confidence: 99%